2017
DOI: 10.1111/ejss.12404
|View full text |Cite
|
Sign up to set email alerts
|

Addition of nitrogen enhances stability of soil organic matter in a temperate forest

Abstract: Physicochemical protection of soil carbon provided by soil aggregates is critical to carbon (C) sequestration in terrestrial ecosystems. However, the stability of soil organic matter (SOM) in terrestrial ecosystems in response to atmospheric nitrogen (N) deposition is unclear. In this study, N was added to a forest soil dominated by deciduous trees on Changbai Mountain, China, at three different rates (0, 25 and 50 kg N ha−1 year−1) from 2007 to 2012. Its effect on C content and stabilization was evaluated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 40 publications
(70 reference statements)
2
20
0
Order By: Relevance
“…LF is a thick and unstable OM, so that its content in the soil tends to be affected by rapid changes that is, influenced by the historical management of soil and forest (Huygens et al, 2005;Dube et al, 2009). The historical processes of logging and cattle grazing with possible greater frequency or intensity in OP cover, could cause less accumulation of OM in the soil, and lost in the physical protection, contributing to the loss of SOM labile (Chen et al, 2017). Our results indicated a LF quantity between 10 and 60 g LF·kg -1 dry soil ( Figure 4A), these values concur with results reported by Huygens et al (2005) for a secondary N. obliqua forest.…”
Section: Physical Fractionation Of Somsupporting
confidence: 89%
See 1 more Smart Citation
“…LF is a thick and unstable OM, so that its content in the soil tends to be affected by rapid changes that is, influenced by the historical management of soil and forest (Huygens et al, 2005;Dube et al, 2009). The historical processes of logging and cattle grazing with possible greater frequency or intensity in OP cover, could cause less accumulation of OM in the soil, and lost in the physical protection, contributing to the loss of SOM labile (Chen et al, 2017). Our results indicated a LF quantity between 10 and 60 g LF·kg -1 dry soil ( Figure 4A), these values concur with results reported by Huygens et al (2005) for a secondary N. obliqua forest.…”
Section: Physical Fractionation Of Somsupporting
confidence: 89%
“…The interaction Depth × Fraction indicated that organic C content is sensitive to soil depth, or pedogenic or environmental characteristics between soil depths ( Figure 4C) (Zagal et al, 2013;Chen et al, 2017).…”
Section: Physical Fractionation Of Sommentioning
confidence: 99%
“…The increased SOC content in fine materials may be due to the input of organic residues ( Fonte et al, 2009 ). At present, studies on the effect of soil available N on SOC in aggregates are mainly focused on farmland ecosystems, and no study on forestland system has been reported yet ( Chen et al, 2017 ). We speculated that the effects of N addition on SOC content in aggregate fractions at forest system might be similar to that of maize cropping systems utilizing organic residues, as both systems return a large amount of plant biomass to soil.…”
Section: Introductionmentioning
confidence: 99%
“…To remove any carbonates (carbonates account for only 0.02% of the dry weight) from the samples, the HCl fumigation method described in Harris, Horwáth, and Kessel (2001) was used before analysis. Therefore, the total C content was equivalent to the organic C content (Chen et al, 2017b).…”
Section: Physicochemical Propertiesmentioning
confidence: 99%
“…Recent studies have focused on the effects of different vegetation types on SOM variability by analyzing lignin in the bulk soil and various soil fractions. However, there is a lack of comprehensive knowledge on the interactions among root extension, aggregates, residue composition, and microorganisms (Angst et al, 2017;Chen et al, 2017b;DeMarco, Filley, & Throop, 2016;Lin & Simpson, 2016;Panettieri, Rumpel, Dignac, & Chabbi, 2017). Spanning more than 200 yr, the distinct successional stages across pioneer broadleaf stands to stably mixed broadleaf-pine stands in the Changbai Mountains in northeastern China (Lou, Zheng, Sui, & Han, 2013;Zhang, Han, & Yu, 2006) provide a unique opportunity to obtain the mechanistic understanding of how vegetation change affects long-term C sequestration.…”
Section: Introductionmentioning
confidence: 99%